Androgenetic alopecia and risk of coronary artery disease - Lata Sharma; Ajay Dubey; P R Gupta; Aruna Agrawal (Wolters Kluwer Medknow Publications, 2013)
Background: Androgenetic alopecia (AGA) or male pattern baldness (MPB) has been found to be associated with the risk of coronary artery disease (CAD). The well-known risk factors are family history of CAD, hypertension, increased body mass index (BMI), central obesity, hyperglycemia, and dyslipidemia. The newer risk factors are serum lipoprotein-a (SL-a), serum homocysteine (SH), and serum adiponectin (SA). Aim : Identifying individuals at risk of CAD at an early age might help in preventing CAD and save life. Hence, a comparative study of CAD risk factors was planned in 100 males of AGA between the age of 25 and 40 years with equal number of age- and sex-matched controls. Materials and Methods : Patients of AGA grade II or more of Hamilton and Norwood (HN) Scale and controls were examined clinically and advised blood test. The reports were available for fasting blood sugar (FBS), serum total serum cholesterol (SC) in 64 cases, 64 controls; lipoproteins (high, low, very low density, HDL, LDL, VLDL), serum triglycerides (ST) in 63 cases, 63 controls; SL-a in 63 cases, 74 controls; SH in 56 cases, 74 controls; and SA in 62 cases, 74 controls. Results : In these cases family history (FH) of AGA and CAD was significantly high. The blood pressure (BP) was also found to be significantly high in the cases. The difference of mean serum HDL, LDL, VLDL, ST, SH, and SL-a in cases and controls were statistically significant and with increasing grade of AGA, the risk factors also increased. Conclusion : Patients with AGA appear to be at an increased risk of developing CAD, therefore, clinical evaluation of cases with AGA of grade II and above may be of help in preventing CAD in future.